The citrus genome - Gmitter Jr., Frederick G.; Wu, Guohong Albert; Rokhsar, Daniel S.; Talón, Manuel (Elsevier, 2021)
The genome of any living organism is the foundation upon which every aspect of that organism’s life is built, including all physical characteristics and interactions with the environment, as well as the mechanisms by which the genome sequence content is passed to offspring. The citrus genome underlies and influences every aspect of citrus trees and fruit, and therefore nearly every chapter topic that follows in this book may best be understood when viewed through the lens of genomic comprehension. A brief history of citrus genome sequencing activities is presented in the historical context of rapidly evolving improvements in genome sequencing technologies, including a summary of de novo genome sequence assemblies. Examples of how the abundance of available citrus genome sequence information has informed studies on the nature of progenitor citrus species, and the contemporary citrus species and the admixtures represented in modern citrus cultivars. Further, the specifics of comparative genome analyses and the conclusions drawn on the evolution and domestication of mandarins are provided. Sequencing technology and associated informatics will continue to improve in the coming years, and the application of the new fundamental information to be generated will support and inform future advances in all the subject areas that follow in this book.